Analysis of the complete lambda light chain germline usage in patients with AL amyloidosis and dominant heart or kidney involvement. - Natalie Berghaus; Sarah Schreiner; Martin Granzow; Carsten Müller-Tidow; Ute Hegenbart; Stefan O Schönland; Stefanie Huhn (PLoS ONE, 2022)
Light chain amyloidosis is one of the most common forms of systemic amyloidosis. The disease is caused by the misfolding and aggregation of immunoglobulin light chains to insoluble fibrils. These fibrils can deposit in different tissues and organs such as heart and kidney and cause organ impairments that define the clinical presentation. In this study, we present an overview of IGLV-IGLJ and IGLC germline utilization in 85 patients classified in three clinically important subgroups with dominant cardiac, renal as well as cardiac and renal involvement. We found that IGLV3 was the most frequently detected IGLV-family in patients with dominant cardiac involvement, whereas in renal patients IGLV1 were most frequently identified. For patients with dominant heart and kidney involvement IGLV6 was the most frequently detected IGLV-family. In more detailed analysis IGLV3-21 was observed as the most dominant IGLV-subfamily for patients with dominant heart involvement and IGLV1-44 as the most frequent IGLV-subfamily in the group of patients with dominant kidney involvement. For patients with dominant heart and kidney involvement IGLV6-57 was the most frequently detected IGLV-subfamily. Additionally, we were able to show an exclusive linkage between IGLJ1 and IGLC1 as well as between IGLJ2 and IGLC2 in the fully assembled IGL mRNA.